Learning Strategies of Teacher the Qur'an Hadith in Improving Student Self Control at Madrasah Aliyah Negeri - Zebua, Nur Ilman; Zein, Achyar; Sahputra, Edi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
Objective: This study was conducted to analyze teacher learning strategies in improving student self-control at Madrasah Aliyah Negeri Gunungsitoli. Methods: This study uses a qualitative research method with a case study approach. This case study will try to examine in detail as well as in-depth a learning strategy for Islamic religious education teachers at Madrasah Aliyah Negeri Gunungsitoli to improve student self-control. Results: Several strategies in increasing student self-control are individual approaches to students, habituation of doing positive things, good program organization, and the formation of shared responsibility in terms of increasing students' self-control which forms knowledge, attitudes, and controls their behavior towards positive, and good and true religious experiences. Supporting and inhibiting factors in increasing the self-control of students at Madrasah Aliyah Negeri Gunungsitoli. In implementing self-control that there are several supporting factors such as principals, teachers, and students providing good support and support all types of programs that are held. The inhibiting factor is that the infrastructure is inadequate for learning given the large number of students who need a conducive learning place. On the other hand, time-limited learning becomes an obstacle considering the few hours of learning that can only be used for delivering the material demanded by the curriculum (syllabus) so that improvements in implementing self-control cannot take place properly.